2020
DOI: 10.1371/journal.pone.0240894
|View full text |Cite
|
Sign up to set email alerts
|

Trends in de-lousing of Norwegian farmed salmon from 2000–2019—Consumption of medicines, salmon louse resistance and non-medicinal control methods

Abstract: The salmon louse Lepeophtheirus salmonis has been a substantial obstacle in Norwegian farming of Atlantic salmon for decades. With a limited selection of available medicines and frequent delousing treatments, resistance has emerged among salmon lice. Surveillance of salmon louse sensitivity has been in place since 2013, and consumption of medicines has been recorded since the early 80’s. The peak year for salmon lice treatments was 2015, when 5.7 times as many tonnes of salmonids were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…The present data set contains a large number of treatments for the most frequently applied delousing methods. The analysis of this data set also confirms the reported national yearly reduction of medicinal treatments and paradigm shift from medicinal to non‐medicinal delousing treatments in Norway (Aaen et al., 2015; Helgesen et al., 2020; Myhre Jensen et al., 2020; Overton, Dempster, et al., 2018). The substantial increase in total number of treatments from year 2016 to 2017 (Table 3) and from year‐class 2015 to 2016 (Table 4) is mainly due to missing production data from year‐class 2015 and 2016 from one company.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The present data set contains a large number of treatments for the most frequently applied delousing methods. The analysis of this data set also confirms the reported national yearly reduction of medicinal treatments and paradigm shift from medicinal to non‐medicinal delousing treatments in Norway (Aaen et al., 2015; Helgesen et al., 2020; Myhre Jensen et al., 2020; Overton, Dempster, et al., 2018). The substantial increase in total number of treatments from year 2016 to 2017 (Table 3) and from year‐class 2015 to 2016 (Table 4) is mainly due to missing production data from year‐class 2015 and 2016 from one company.…”
Section: Discussionsupporting
confidence: 80%
“…Over a long time period, large‐scale reliance on a few chemotherapeutants to control salmon lice has resulted in a drift towards resistance (Denholm et al., 2002; Myhre Jensen et al., 2020). Today, salmon lice display reduced sensitivity and/or resistance towards all available chemotherapeutants, except benzoylphenyl ureas (Aaen et al., 2015; Helgesen et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…skirts and snorkels] and selective breeding). Lice have evolved resistance to at least 4 of 5 chemical therapeutants (Aaen et al 2015, Myhre Jensen et al 2020, and while evidence is incomplete for the other louse control methods, Coates et al (2021) concluded that the evolution of resistance to non-chemical methods is a strong possibility given the variation that exists in and between louse populations (Jacobs et al 2018) on which non-chemical selection pressures could act and that this variation may have a genetic basis.…”
Section: Implications For Salmon Lice Ecology and Evolutionmentioning
confidence: 99%
“…Instead, organophosphates, pyrethroids and hydrogen peroxide were reintroduced. The initial effect was good, but the problems with resistance reappeared quickly [ 21 ].…”
Section: Introductionmentioning
confidence: 99%